-7(-1+3x)=5(3-5x)

Simple and best practice solution for -7(-1+3x)=5(3-5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-1+3x)=5(3-5x) equation:


-7(-1+3x)=5(3-5x)

We simplify the equation to the form, which is simple to understand
-7(-1+3x)=5(3-5x)

Reorder the terms in parentheses
+(+7-21x)=5*(3-5x)

Remove unnecessary parentheses
+7-21x=+5+*(+3-5x+)

Reorder the terms in parentheses
+7-21x=+(+15-25x)

Remove unnecessary parentheses
+7-21x=+15-25x

We move all terms containing x to the left and all other terms to the right.
-21x+25x=+15-7

We simplify left and right side of the equation.
+4x=+8

We divide both sides of the equation by 4 to get x.
x=2

See similar equations:

| 35(8x-20)-18=-718 | | 6(x-4)=-5(2x+2) | | m^2-8m-33=0 | | x+3+2x+5=19 | | l^2-6l-91=0 | | -6-x=15+2x | | 3p(-4)=13 | | 3(x-2)+4=2x+6 | | 13.95x=558 | | 5x/2+x/2+2=3x | | x+(x+2)=0 | | 15-3(6-2c)= | | 13b+44=4 | | 2(x+3)=3-x | | 3-5(2x+3)=20 | | -5y+7=-2(y-5) | | -z=40 | | 6x+5-3x=-22 | | 13.95x=279 | | 6y^2-15y=0 | | 20=-x | | 5n=6 | | 3b+25=8(10+b) | | a/2=2 | | -8=6n-3-7n | | 6*2-0.5*24= | | x/4-3=2x/5 | | 2x=2.6+1.4 | | 1-32x=2+31x | | -3(36+7x)=-66 | | 9x/4+2/5=49/10 | | 5(y+10)=4 |

Equations solver categories